Pengaruh Waktu Pengomposan Limbah Debu Sabut Kelapa dengan Kotoran Ayam Terhadap Kualitas Kimia Kompos dan Pertumbuhan Tanaman Pakcoy (Brassica chinensis) - Jaliya Anjana (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2022)
The long fermentation chain of coconut husk dust waste needs the addition of a bioactivator to speed up the composting process. Chicken manure is an opportunity for natural activators in the fermentation process of coconut husk dust waste. The time required in composting waste will be more optimal with the addition of bioactivators such as EM-4. The research was conducted at the organic fertilizer manufacturing site 'Minak Jinggo' which is located in Sumberbaru Village, Singojuruh District, Banyuwangi Regency and continued the analysis at the Soil Science Study Program Laboratory, Faculty of Agriculture, University of Jember. In the first coronation design using a Complete Randomized Design (RAL) with one factorial and 7 treatments. Compost content testing was carried out which included analysis of measuring pH, N, P. K, C-Organic and C / N ratio of compost. Compost results with time and content in accordance with Kepmentan No. 261 of 2019 were then designed an effect test experiment on mustard pakcoy plants with 2 factorials, namely the compost used and the dosage. Done with replays 3 times each treatment. The variables observed included plant height (cm), total number of leaves (strands), stem diameter (cm), plant leaf area (cm3), total fresh weight of the plant (g) and total dry weight of the plant (g). The data obtained will then be analyzed descriptively and statistically using Anova variety analysis at the level of 5% and an Honest Real Difference Test (BNJ) at a level of 95% confidence (P<0.05) to determine the differences between treatments. The comparative treatment of coconut husk dust waste material and chicken manure 30:70 with a composting time of 28 days is the right compost formulation and effect composting time to become compost in accordance with Kepmentan No. 261 of 2019 with an NPK content of 2.074%, C-Organic of 18.47, and A C/N ratio of 11.76. Compost treatment and the best doses on the growth and yield of pakcoy plants are in the treatment of adding compost with a ratio of 30:70 (K3) material and a dose of 20 tons perhektar (D2) which affects plant height growth, number of leaves, dry weight of plants, N content of plants, and the highest absorption of plant N. As for the wet weight of the plants, the highest is found in the compost addition treatment with a material ratio of 50:50 (K2) and a dose of 20 tons perhektar (D2).